2012
DOI: 10.1155/2012/315467
|View full text |Cite
|
Sign up to set email alerts
|

Serum Galactose-Deficient IgA1 Level Is Not Associated with Proteinuria in Children with IgA Nephropathy

Abstract: Introduction. Percentage of galactose-deficient IgA1 (Gd-IgA1) relative to total IgA in serum was recently reported to correlate with proteinuria at time of sampling and during follow-up for pediatric and adult patients with IgA nephropathy. We sought to determine whether this association exists in another cohort of pediatric patients with IgA nephropathy. Methods. Subjects were younger than 18 years at entry. Blood samples were collected on one or more occasions for determination of serum total IgA and Gd-IgA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 27 publications
4
15
0
Order By: Relevance
“…Serum Gd-IgA1 level did not associate with degree of proteinuria for adults [28,32] or children [48]. In a study that combined pediatric and adult patients, absolute serum Gd-IgA1 level did not correlate with decline in estimated GFR (eGFR) or degree of proteinuria at biopsy, but an elevated percent of Gd-IgA1/total IgA correlated with these clinical risk factors [32].…”
Section: Biomarkers Of Iga Nephropathymentioning
confidence: 99%
“…Serum Gd-IgA1 level did not associate with degree of proteinuria for adults [28,32] or children [48]. In a study that combined pediatric and adult patients, absolute serum Gd-IgA1 level did not correlate with decline in estimated GFR (eGFR) or degree of proteinuria at biopsy, but an elevated percent of Gd-IgA1/total IgA correlated with these clinical risk factors [32].…”
Section: Biomarkers Of Iga Nephropathymentioning
confidence: 99%
“…Some studies have suggested that variants of galactose-deficient IgA1(Gd-IgA1) are more common in the sera of IgAN patients compared with the sera of healthy individuals or with sera from patients with other types of renal disease[4,5]. Furthermore, some researchers have reported that the level of Gd-IgA1 in the sera of patients with IgAN is associated with disease progression[6], though others have found that serum Gd-IgA1 level is not associated with proteinuria in children with IgAN[7]. In the current study, a meta-analysis was done to determine differences in Gd-IgA1 serum levels between IgAN patients and healthy controls and to clarify whether serum assays for Gd-IgA1 are reliable and useful for predicting renal pathological progression of IgAN.…”
Section: Introductionmentioning
confidence: 99%
“…The development of a monoclonal antibody specific to Gd-IgA1 could offer a new appropriate biomarker [18]; however, using this specific test, only one third of IgAN patients had values higher than those of other diseases. Levels of Gd-IgA1 in children were related neither to proteinuria [15] nor to treatment outcome in our IgACE trial [19]. Moreover, Gd-IgA1 are increased in patients, but also in healthy relatives [20].…”
Section: Biomarkers Specific To Iganmentioning
confidence: 64%
“…In patients with IgAN there is a high frequency of O-glycans consisting of GalNAc alone due to defective galactosylation (Gd-IgA1) [1,2]. Although Gd-IgA1 is a rather sensitive and specific marker for IgAN, as reported by most studies (with a sensitivity of 56-76 % and a specificity of 89-94 %) [14][15][16], discrepancies exist likely because of the technical pitfalls for detecting Gd-IgA1 based on lectin binding assays [17]. The development of a monoclonal antibody specific to Gd-IgA1 could offer a new appropriate biomarker [18]; however, using this specific test, only one third of IgAN patients had values higher than those of other diseases.…”
Section: Biomarkers Specific To Iganmentioning
confidence: 99%
See 1 more Smart Citation